Przyczyny i procedura wydalania duchownych z instytutu zakonnego - Skorupa, Ambroży (Prawo Kanoniczne, 2011)
A religious in an institute fulfills his vocation by following the way adequate to the charism of the institute. An attitude unsuited to a religious’ priestly vocation as well as to the institute’s charism, can be the cause of dismissal from religious institute. Among the causes of dismissal can be diffusion of doctrine inconsistent with the magisterium of the Church or an attitude incompatible with position of the Church. In the article were presented some exemplary statements of the Congregation for the Doctrine of the Faith regarding doctrinal and moral questions. Stubborn diffusion of views recognized by the Holy See as opposed to the Catholic doctrine, may be another cause for dismissal from an institute. Dismissal from religious institute may also result from an attitude incompatible with the ecclesiastical and religious discipline. Attitudes causing grave scandal require reaction of the competent religious superiors. The superiors are obliged to act in accordance with the process regulated by the norms included in the CCL 1983 and in other ecclesiastical documents. Choosing proper process depends on the nature of an offense committed by a religious. For offenses described in can. 694 a religious is dismissed by the fact itself of committing the offense (ipso facto). Therefore the process described in the cannon for this form of dismissal must be kept. In instances of offenses described in cannons 695 and 1395, for which the legislator provided an obligatory dismissal, the process is different. In case of offenses pointed out in can. 696 the superior is obliged to initiate process indicated in can. 697. The right of the accused to self-defense, participation of a notary in the process, required decision by the major superior and approval of a decree by ecclesiastical hierarchical authority – the Holy See or diocesan bishop, depending on the approval level of the institute, deserves attention.